Advanced Formulation of White Adhesive with Enhanced Bonding Strength Using Polyvinyl Acetate (PVA) and Acrylic Additives - Nnadikwe johnson; Iheme Chigozie; Nwosi Hezekiah Andrew (Sean Institute, 2025)
An adhesive, known by various names such as glue, cement, mucilage, or paste, is a material applied to one or both surfaces of two distinct items to unite them and withstand any attempts to pull them apart. Adhesives can occur naturally or be artificially manufactured. In this specific context, the discussion centers on the utilization of acrylic and polyvinyl acetate (PVA) as the base materials for the adhesives under consideration.,In the process of formulating the adhesive, approximately 2 liters of water were measured and then poured into a plastic bucket, which served as the mixing vessel. Subsequently, 0.7 kg of calcium carbonate was introduced into the water-filled bucket and stirred for thorough blending. Following this, 0.5 kg each of acrylic and polyvinyl acetate (PVA) were added to the mixture in the bucket and stirred diligently until a uniform and well-integrated blend was achieved.Subsequently, 0.1 kg of nitrosol and 0.07 kg of bamacol powder were incorporated into the mixture, followed by continuous stirring to ensure a uniform blend. Additionally, 0.05 kg of formalin was introduced as a preservative and stirred for approximately ten minutes to finalize the product. The adhesive's performance was then evaluated by testing its bonding properties on various material combinations, including wood-to-wood, carton-to-carton, paper-to-paper, wood-to-metal, and paper-to-wood applications.The results indicated that the white adhesive serves as a versatile, multipurpose product when applied. Various properties such as drying time, bonding strength, and pH levels were tested to determine the optimal qualities of the adhesive. Additionally, the shelf life of the formulated adhesive was thoroughly examined. Ultimately, the adhesive demonstrated its effectiveness in bonding paper-to-paper, paper-to-wood, and other packaging materials, showcasing its versatility and practicality in various applications.